Managing complications of endoscopic transsphenoidal surgery in pituitary adenomas. Issue 5 (2nd September 2020) - Abhinav, Kumar; Tyler, Matthew; Dale, Oliver T.; Mohyeldin, Ahmed; Fernandez-Miranda, Juan C.; Katznelson, Laurence
ABSTRACT: Introduction: Over the last two decades there has been a gradual shift from the traditional microscopic approach toward the use of endoscopic endonasal approach for resection of pituitary adenomas. Multiple medical and surgical complications can occur following endoscopic transsphenoidal resection of adenomas. Areas covered: We discuss the evolution of the surgical practice from the use of the 'microscope' to the 'endoscope' in the resection of pituitary adenomas. We present a comprehensive review of the medical and surgical complications following surgery with particular emphasis on both the prevention and management of electrolyte disturbance, cerebrospinal fluid leak and the rare but dreaded complication of internal carotid injury (ICA). We also searched the PubMed database to identify relevant literature between 1984 and 2019. Expert opinion: Use of endoscope compared with microscope may be associated with better preservation of pituitary gland function with similar extent of resection. Overall medical and surgical complications can be safely managed in high volume centers in association with endocrinologists and skull base trained otolaryngologists. Understanding of anatomico-technical nuances and meticulous surgical technique are important toward preventing ICA injury. Ongoing surgical and technical developments coupled with imaging advances will likely lead to better future outcomes for patients with functioning and nonfunctioning adenomas.